Book Reviews (Res Medica, 2013)
CLINICAL CHEMISTRY IN PRACT ICAL MEDICINE, by C. P. Stewart and Sir Derrick Dunlop. Sixth Edition, published by E. & S. Livingstone, Ltd., Edinburgh, 1962. Pp. 359. Price 27s. 6d.In this latest edition of a well proven and universally accepted textbook, there have been few major changes, reflecting the great popularity of previous editions. The revision has included recent advances insofar as they are significant in clinical medicine.